Kepatuhan Memediasi Pengaruh Kesadaran, Reformasi dan Persepsi atas Sanksi terhadap Penerimaan Pajak Daerah - Yasa, I Nyoman Putra; Kesawa, Angga Putra; Dewi, Ni Made Puspa (Jurnal Ilmiah Akuntansi, 2020)
This study aims to examine the effect of awareness of taxpayers, tax administration reforms and perceptions of tax sanctions on vehicle tax revenues in Buleleng Regency of Bali with taxpayer compliance as a moderating variable. Survey method through the distribution of questionnaires as data collection instruments is conducted. Multiple linear regression analysis is used to analyze the relationship between taxpayer awareness variables, tax administration reform, the perception of tax sanctions and tax compliance. Also, to examine the mediating role it is using path analysis and Sobel test. The results of this study indicate that taxpayer awareness, tax administration reforms, and perceptions of tax sanctions have a significant influence on motor vehicle tax revenue bothÂ directly and indirectly throught taxpayer compliance.